Transient Glass Formation around a Quadrupolar Photoexcited Dye in a Strongly H‐Bonding Liquid Observed by Transient 2D‐IR Spectroscopy. (26th November 2018) - Dereka, Bogdan; Helbing, Jan; Vauthey, Eric
Abstract: Intermolecular H‐bonding dynamics around a photoexcited quadrupolar dye is directly observed using transient 2D‐IR spectroscopy. Upon solvent‐induced symmetry breaking, the H‐bond accepting abilities of the two nitrile end‐groups change drastically, and in extremely protic (superprotic) solvents, a tight H‐bond complex forms at one end. The time evolution of the 2D C≡N lineshape in methanol points to rapid, 2–3 ps, spectral diffusion due to fluctuations of the H‐bonding network. Similar behavior is observed in a superprotic solvent shortly after photoexcitation of the dye. However, at later times, the completely inhomogeneous band does not exhibit spectral diffusion for at least 5 ps, pointing to a glass‐like environment around one side of the dye. About half of the excited dyes show this behavior attributed to the tight H‐bond complex, whereas the others are loosely bound. A weak cross peak indicates partial exchange between these excited state subpopulations. Abstract : Zähe Angelegenheit : Einige Pikosekunden nach seiner Anregung bildet ein quadrupolarer Farbstoff einen engen und asymmetrischen Wasserstoffbrückenkomplex mit dem Lösungsmittel. Transiente 2D‐IR‐Spektroskopie offenbart, dass dieser Vorgang in einer drastischen Verlangsamung der Lösungsmitteldynamik an einer Seite des Farbstoffs resultiert. Das umgebende Lösungsmittel zeigt ein glasähnliches Verhalten.